The fire of religions and beliefs in the book "the animal" of the mazhars - زردة يوسف (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
In this research, we tried to shed light on the great importance of talking about fire in general, and about the fire of beliefs and religions in particular, and we touched on his motives to care for this subject in a book he called "animal". Based on the words of the same preacher in the book’s reworking, not on expected or disheartening reasons, and then we referred to the kinds of fires that the preacher talked about, from normal physical fires, by which God had perished on creation, so that they could use them on many of their daily life affairs. We then talked about other metaphorical fires, the greatest of which is Islam, and mentioned in the Qur’an, KunarJhnam, the fire that was cold and peaceful on our Lord Abraham, and the fire that Allah revealed to our Lord Moses on the Mount of the Tur, the fire of the Israelites, and the fire of "two Els" that was on Khaled Bin Sinan Al-Asan We have also highlighted this search on the fire site of the Hindu religion; As the only religion that did not recognize metaphorical fire, and did not know of the physical or ordinary fire that it had set up, or linked to the sacred, it differed from the Islamic religion, which did not see in the normal material fire unobbed by God, Jalila al-Jushayeh, which was of low cost. We concluded by trying to show the way of preaching the cognitive vocabulary that he used in his talk about fire, and we referred to his swing between commenting on some vocabulary terms from Qur’anic verses, and prophetic talk only in the words of a few words, and taking it - sometimes - from some of these words as a starting point. Or as a pretext for going on to engage in matters of rhetoric or language.